Flow velocity behavior programming on open channel bends. Issue 1 (October 2021) - Setiyadi, S
Abstract: Flow velocity on open channel bends generally experiences additional velocity which is called secondary velocity. This paper aims to analyse and calculate the velocity that occurs in an open channel bend in general. The calculation that the writer uses is the calculation with fortran programming, in a case study of a river that bends, where the variables that must be present are given. The results of calculations and measurements of Secondary Speeds that occur at channel bends in this Open Channel will be very useful for river channel improvement or flood prevention in river channels, especially on existing bends. The conclusion is that at the bend of an open channel or river, there will be an increase in flow velocity in the transverse direction. This additional velocity is caused by the additional secondary velocity, namely the transverse velocity.